(untitled) (Journal of Global Accounting, 2024)
The study explored the effect of contributory pension scheme on the growth of Nigerian economy. The study specifically examined the effect of contributory pension fund on GDP, capital market development and infrastructural development of Nigeria. The population of the study consisted of twenty one (21) Pension Funds Administrators (PFAs) operating in Nigeria as at 31st December, 2022. The sample size of the study was made up of ten (10) pension fund administrators in Nigeria using purposive sampling techniques. The study made use of time series data which were obtained from Central Bank of Nigeria (CBN) statistical bulletin, world development indicator, National Pension Commission, annual reports and accounts of PFAs. The study employed the Ordinary Least Square (OLS) simple regression to analyse the data. The findings showed that contributory pension fund has a significant effect on GDP, capital market development and infrastructural development of Nigeria. The study therefore conclude that contributory pension scheme significantly affects the economic growth of Nigeria. The study thus recommended among others that idle pension funds should be invested in infrastructural development and the other sectors that will boost the GDP of the economy.